Antitumor Mechanisms of Active Ingredients from Traditional Chinese Medicine and Advances in Modern Drug Translation - Yuru Mao (GBP Proceedings Series, 2026)
Traditional Chinese medicine resources possess rich chemical skeletons and long-standing medicinal experience, making them an important source for the discovery of antitumor lead compounds. This article focuses on artemisinin, camptothecin, triptolide, berberine, ginsenosides, and arsenic trioxide, which have well-defined chemical structures, relatively sound mechanistic research, and represent different stages of translation. It summarizes their antitumor effects around cell proliferation and death, DNA damage, oxidative stress and ferroptosis, invasion and metastasis, and the tumor microenvironment. Furthermore, it analyzes modern drug translation pathways from aspects such as structural modification, pharmacokinetic improvement, drug delivery systems, combination therapy, and clinical evidence grading. Current evidence indicates that camptothecin derivatives and arsenic trioxide have formed relatively mature clinical translation paradigms, while triptolide, artemisinin derivatives, berberine, and ginsenosides demonstrate different stages of progress from mechanism discovery to candidate drugs and combination therapies. Future research should strengthen the causal link between direct targets and in vivo exposure, improve quality control, therapeutic window evaluation, and stratified clinical validation, thereby increasing the efficiency of the transformation of active ingredients of traditional Chinese medicine into modern anti-tumor drugs.